The Effect of Parent Attachment, Teacher Support, and Learning Motivation on Science Learning Outcomes of Elementary School Students in Kecamatan Gajahmungkur - Rusli, Tiffany Shahnaz; Wahyudin, Agus; Lestari, Wahyu (Educational Management, 2021)
This study aims to obtain evidence concrete about the effect of parental attachment, teacher support, and learning motivation on science learning outcomes of elementary school students. This study uses a quantitative approach. The population of the study was 189 students of class V SDN Gajahmungkur in the academic year 2019/2020 with a sample of 128. The sampling technique used two stage random sampling. The data collection technique used unstructured interview techniques, questionnaires, and documentation. The data analysis technique used descriptive and inferential statistical analysis techniques. The results showed that parental attachment had a significant direct effect of 23.9% on student learning outcomes. Teacher support has a direct effect of 29.9% on students' science learning outcomes and learning motivation has a significant direct effect of 29.1% on science learning outcomes of elementary school students.